Contrast sensitivity and visual acuity under low light conditions in macular telangiectasia type 2. Issue 3 (1st June 2018) - Müller, Simone; Heeren, Tjebo F C; Bonelli, Roberto; Fruttiger, Marcus; Charbel Issa, Peter; Egan, Catherine A; Holz, Frank G
Abstract : Background/Aim: Macular pigment optical density (MPOD) is centrally depleted early on in macular telangiectasia type 2 (MacTel). Contrast sensitivity (CS) might be related to MPOD, and thus impaired in early MacTel. The effect of low luminance was assessed on both CS and best corrected visual acuity (BCVA). Methods: This is a cross-sectional study. Pelli-Robson charts were used for CS testing at 1 m in photopic (110 lux) and mesopic (1 lux) conditions. BCVA was tested with ETDRS charts and low luminance visual acuity (LLVA) with a 2.0 log unit neutral density filter. MPOD was obtained with dual-wavelength autofluorescence. Results: One hundred and three eyes of 52 patients with MacTel (mean±SD age 62.9±10.2, range 35–77) were compared with 34 healthy eyes of 17 controls (mean±SD age 65.2±7.4, range 53–78). CS was significantly lower in the eyes with MacTel. This impairment was higher in low light conditions (low light contrast sensitivity (LL-CS)). Eyes at the early stages of MacTel had significantly lower LL-CS than controls, but normal (photopic) CS. The results were similar but less pronounced for BCVA/LLVA. Decrease in CS was correlated with loss of MPOD. Conclusions: Low light conditions have a detrimental effect on visual performance in MacTel. Impaired CS might correlate with MPOD depletion as a pathognomonic finding in MacTel. Functional impairment might precede structural disintegration, indicating dysfunction at the cellular level. The applied tests might be useful as additional functional assessments in clinical routine and as outcome measures in future interventional clinical trials.